Haemophilus influenzae corneal ulcer in a therapeutic contact lens wearer. Issue 3 (March 1984) - Armstrong, J. R.; Cohen, K. L.; McCarthy, L. R.
Abstract : Haemophilus influenzae is an unusual corneal pathogen and an unusual cause of corneal ulcers in Western society. In previous reports corneal complications from H. influenzae have been secondary to a conjunctivitis. The first case of a primary H. influenzae corneal ulcer as a complication of therapeutic contact lens wear is presented. Since other uncommon bacteria have been reported as causes of contact lens related corneal ulcers, the bacteriology of contact lens related corneal ulcers is reviewed. Ophthalmologists need to be aware that H. influenzae infections in adults are becoming more frequent.